Objects in seas of relationships: teaching experiences of Atlantic History in museums - Limírio Chaves, André (Universidad Nacional del Litoral, 2019)
The objective of this article is to present and analyze teaching experiences in museum spaces, which set out to translate the precepts and concepts of Atlantic History from the creation of new strategies for the approach and interpretation of collections. For this will be addressed the planning, curating and assembly processes of two exhibitions that took place in museums and galleries in the city of Belo Horizonte (Minas Gerais, Brazil), in which they sought to make visible the networks and connections that integrated the Atlantic spaces, in the first modernity, and give new projection to the human experiences forged in the transits between geographies and in the meeting of cultures.